Black Jacks : African American Seamen in the Age of Sail. - Bolster, W. Jeffrey (Harvard University Press, 2009)
Aiming to reveal the role sailors played in helping forge new identities for black people in America and how they actively contributed to the Atlantic maritime culture, this book traces the history of black seamen to the end of the American Civil War.